A clinical study incorporating multimodal 18F-FDG PET/CT metabolic parameters, genetic markers, and clinical characteristics for the evaluation and prediction of treatment efficacy and prognosis in Langerhans cell histiocytosis - Huang, Zizhen; Qi, Wanling; Rao, Tian; Zeng, Qingyun; Lu, Ping; Zhang, Jie; Qiu, Zhibin; Xiao, Guihua; Liu, Qian; Fu, Huan; Liao, Fengxiang (Frontiers in Medicine, 2025)
ObjectivesLangerhans cell histiocytosis (LCH) is a rare clonal proliferative disorder characterized by the infiltration of pathological Langerhans cells into multiple organs, exhibiting significant clinical heterogeneity. Although standard chemotherapy regimens have markedly improved patient survival rates, several challenges remain, such as low response rates, high recurrence rates, and long-term sequelae in certain patients. This study aimed to integrate multimodal 18F-FDG PET/CT metabolic parameters, genetic markers, and clinical characteristics to evaluate and predict treatment efficacy and prognosis in patients with LCH.MethodsA retrospective analysis was conducted on clinical data and 18F-FDG PET/CT imaging findings from 26 patients diagnosed with LCH via biopsy pathology between May 2016 and December 2024 at the Department of Nuclear Medicine, Jiangxi Provincial People’s Hospital. Four metabolic parameters—SUVmax, TLR, MTV, and TLG—as well as genetic markers and clinical features (e.g., gender, age, type, stage) were evaluated. All patients were followed up for at least 1 year or until disease progression or relapse occurred. Univariate and multivariate analyses were performed to assess progression-free survival.ResultsPatients with disease progression or recurrence exhibited significantly higher SUVmax, TLR, MTV, and TLG values compared to those who responded to treatment. ROC curve analysis identified optimal cutoff values for predicting disease remission as follows: SUVmax = 7.5, TLR = 5.2, MTV = 25.0, and TLG = 150. The remission rates in the high-value groups for SUVmax, MTV, and TLG were significantly lower than those in the corresponding low-value groups, with the most pronounced differences observed in the MTV and TLG groups (p < 0.01). TLG demonstrated the highest AUC value (0.91), indicating its strong predictive power. Clinicians should be vigilant about recurrence risk when MTV ≥ 25.0 or TLG ≥ 150.0. In univariate analysis, classification as multisystem LCH with risk-organ involvement (MS-LCH RO+), Ann Arbor stage III, BRAF V600E positivity, MTV > 25.0, and TLG > 150.0 were significant risk factors for worse progression-free survival (PFS) (all p < 0.05). Furthermore, patients in the high SUVmax, high MTV, and high TLG groups exhibited significantly shorter PFS. Multivariate Cox regression analysis identified the metabolic parameters MTV and TLG as independent predictors of PFS. The BRAF V600E mutation rate was significantly higher in patients with MS-LCH and those in the high SUVmax and high TLG groups.ConclusionBaseline metabolic parameters derived from 18F-FDG PET/CT represent promising imaging biomarkers for predicting therapeutic response and prognosis in LCH. When integrated with established clinical stratification systems, these metabolic indices facilitate a more comprehensive multidimensional prognostic evaluation framework.